The Influence of Leadership Style and Work Motivation on Employee Performance with Job Satisfaction as an Intervening Variable (Study at Prima SR Hotel & Convention Yogyakarta) - Yeli Yikwa; Catrina Yunita Wenda; Gita Sugiyarti (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
Leadership style, motivation and job satisfaction are part of the factors which affects performance. The purpose of this study is to determine the effect leadership style and motivation on performance through job satisfaction as an intervening variable. This research is also intended to determine the effect of style leadership and motivation on performance through job satisfaction as a variable intervene directly and indirectly. This research is done to 50 employee respondents of Prima SR Hotel & Convention Yogyakarta. Method the research used is a quantitative method using statistical and descriptive analysis. The results of this study are (1) There is an influence of leadership style significant positive effect on job satisfaction. (2) there is a stylistic influence leadership has a significant positive effect on performance. (3) there is influence positive and significant work motivation on job satisfaction. (4) there is influence positive and significant work motivation on performance. (5) there is an influence positive and significant job satisfaction on performance. (6) the influence is not direct leadership style on employee performance through job satisfaction greater than the direct influence of leadership style on performance employees (7) the direct effect of motivation on employee performance is greater rather than the indirect influence of motivation on employee performance through job satisfaction.